Analysis of Gender, Self- Readiness, and Stress in the Implementation of Psychological First Aid - Sudjiwanati; Pinastikasari, Nindita (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Self-readiness is one aspect that can influence adolescents in facing life's problems. Students, both male and female, who are still in the adolescent development stage can experience problems, namely a lack of knowledge about self-preparation in facing life's problems that can cause stress and also a lack of psychological first aid skills ( First Psychological Aid ) for themselves and others. Lack of student knowledge about self-preparation and First Psychological Aid can increase stress and ultimately affect student academic achievement. Likewise, gender differences between men and women can also be a factor that influences how adolescents face life's problems. The purpose of this study was to determine the effect of gender on self-preparation in learning, dealing with stress and first aid in students of the Faculty of Psychology, Wisnuwardhana University, Malang. The research methodology used is a quantitative descriptive research method with a sample of 203. Measurements were carried out using a scale of self-preparation, stress and First Psychological Aid ( PFA) collected through Google Form media . The results of data analysis using the Manova test showed that the f value of Gender on the dependent variable of self-preparation, stress, and Psychological First Aid had a significance value of 0.870; 0.292; 0.160 > 0.05, which means that gender does not significantly influence self-preparation, stress, and Psychological First Aid. Based on the results of this study, it can be concluded that male and female students who have knowledge of PFA can prepare themselves and have the ability to manage stress in carrying out study tasks and in daily life.